ANALYSIS OF THE EFFECT OF JOB SATISFACTION AND WORK COMPETENCE ON EMPLOYEE WORK PRODUCTIVITY, MEDIATED BY WORK MOTIVATION - Parlin Swantono Panjaitan; Fajar Rezeki Ananda Lubis; Salman Faris (Nurul Jadid University, 2025)
This study aims to analyze the influence of Motivation as a mediating variable in the relationship between Job Satisfaction and Job Competence on Work Productivity among permanent employees of PT. Jatim Jaya Perkasa. Given a population of 1,071 people, this study used purposive sampling to select 95 respondents as the sample. Data were collected through questionnaires and secondary documentation studies, which were then processed quantitatively using SPSS version 28 through a series of tests: t-test, Sobel test, and path analysis. The research findings reveal that all hypotheses were empirically proven. Job satisfaction and competence were proven to have a positive and significant impact on both motivation and productivity. Furthermore, the discussion of the results of the analysis conducted by the researcher can be concluded that the Motivation variable has such an effective influence that it functions as a mediator connecting satisfaction and competence in an effort to increase employee productivity at PT. Jatim Jaya Perkasa